Use and prevalence of contraception in some countries of the American region - Freeman, Helen R. (PAHO Washington, DCUS, 1984)
Describes the current state of contraceptive use in the American region concentrating on countries which have been the subject of contraceptive prevalence-type surveys. However, includes brief discussion on contraceptive use in countries which were not the subjects of contraceptive prevalence-type surveys. Discusses prevalence of contraceptive use and methods, age group differences for different methods, and the sources of contraceptives supply. Includes population data, statement on population policy, and the sources of information on contraceptive behaviour for each country.